Phylogenetically independent behavior mediating geographic distributions suggests habitat is a strong driver of phenotype in crangonyctid amphipods - Worsham, McLean L. D.; Nair, Parvathi; Gibson, J. Randy; Rodriguez, David; Schwartz, Benjamin F.; Nowlin, Weston H. (Frontiers in Ecology and Evolution, 2023)
It is unclear if geographic distributions of animals are behaviorally mediated or simply maintained by ecologically-driven deleterious effects on fitness. Furthermore, it is not well known how behaviors that may affect geographic distributions and responses to environmental stressors evolve. To explore this, we examined behavioral and physiological reactions to light in six species of amphipods in the family Crangonyctidae collected from a variety of subterranean and epigean habitats. Stark differences between epigean and subterranean habitats occupied by different crangonyctid species allowed this clade to serve as an appropriate model system for studying the link between habitat and phenotype. We sampled habitats in or adjacent to the Edwards Aquifer in central Texas and collected two epigean and four stygobiontic species. We examined respiratory and behavioral responses to light in all study species. We found that similarities in behavioral and physiological responses to light between species were only weakly correlated with genetic relatedness but were correlated with habitat type. However, the breadth of variation in phenotype was found to be correlated with phylogenetic relationships, suggesting that population level trait evolution likely involves interactions between standing population level variation and strength of selection. Our findings suggest that natural selection via environmental conditions may outweigh history of common ancestry when predicting phenotypic similarities among species, and that behavioral and physiological phenotypes may mediate the evolution of biogeographic distributions.